# Hypotenuse and height

In a right triangle is length of the hypotenuse c = 56 cm and height hc = 4 cm. Determine the length of both trangle legs.

Result

a =  55.9 cm
b =  4 cm

#### Solution:  Leave us a comment of example and its solution (i.e. if it is still somewhat unclear...): Be the first to comment! #### To solve this example are needed these knowledge from mathematics:

Looking for help with calculating roots of a quadratic equation? Do you have a linear equation or system of equations and looking for its solution? Or do you have quadratic equation? See also our right triangle calculator. See also our trigonometric triangle calculator.

## Next similar examples:

1. Euclid3 Calculate height and sides of the right triangle, if one leg is a = 81 cm and section of hypotenuse adjacent to the second leg cb = 39 cm.
2. Euclid1 Right triangle has hypotenuse c = 27 cm. How large sections cuts height hc=3 cm on the hypotenuse c?
3. Catheti The hypotenuse of a right triangle is 41 and the sum of legs is 49. Calculate the length of its legs.
4. Euclid2 In right triangle ABC with right angle at C is given side a=27 and height v=12. Calculate the perimeter of the triangle.
5. Triangle ABC In a triangle ABC with the side BC of length 2 cm The middle point of AB. Points L and M split AC side into three equal lines. KLM is isosceles triangle with a right angle at the point K. Determine the lengths of the sides AB, AC triangle ABC.
6. Isosceles IV In an isosceles triangle ABC is |AC| = |BC| = 13 and |AB| = 10. Calculate the radius of the inscribed (r) and described (R) circle.
7. Roots Determine the quadratic equation absolute coefficient q, that the equation has a real double root and the root x calculate: ?
8. Discriminant Determine the discriminant of the equation: ?
9. Equation Equation ? has one root x1 = 8. Determine the coefficient b and the second root x2.
10. Theorem prove We want to prove the sentence: If the natural number n is divisible by six, then n is divisible by three. From what assumption we started?
11. Solve 3 Solve quadratic equation: (6n+1) (4n-1) = 3n2 Find the roots of the quadratic equation: 3x2-4x + (-4) = 0. Eequation f(x) = 0 has roots x1 = 64, x2 = 100, x3 = 25, x4 = 49. How many roots have equation f(x2) = 0 ? Solve this equation: x + 5/x - 6 = 4/11 Find variable P: PP plus P x P plus P = 160 Solve equation: log33(3x + 21) = 0 If 5x + x² > 100, then x is not